Análisis de un método activo para la detección de isla basado en la perturbación de la fase en el pll y comparación con otros métodos activos - Trujillo Rodríguez, Cesar L.; Velasco de la Fuente, David; Figueres Amorós, Emilio; Garcerá Sanfeliú, Gabriel (Revista Científica, 2011)
This paper presents a new active anti-islanding detection method for distributed power generation systems. This method is based on introducing a disturbance at the inverter output and observing the behavior of the voltage at the point of common coupling (PCC), which depends on the impedance connected to the PCC in an islanding situation. Additionally, this paper presents the analysis and comparison of the main active techniques for islanding detection and these were compare with the proposed technique. The algorithms mentioned in this work were simulated in PSIMTM in order to make a comparative analysis and to establish their advantages and disadvantages according to IEEE standards.